Impact of size of the manufacturing firms on knowledge management practices: an empirical analysis - S.D. Uma Mageswari; Chitra Sivasubramanian; T.N. Srikantha Dath (Penerbit Universiti Kebangsaan Malaysia, 2015)
Manufacturing sector is the driver of economic growth of developing countries and employment. Knowledge and knowledge management result in manufacturing excellence by improving productivity and flexibility of the organizations’ operations. This study has identified four fundamental knowledge management processes from the literature, namely knowledge acquisition, knowledge creation, knowledge storage and knowledge sharing that contribute to the growth of the organizations. Thus, we had developed a questionnaire to analyze these processes in the Indian manufacturing sector. Confirmatory factor analysis was performed using LISREL (Linear Structural Relations) software, that is, to test the convergence of the observed variables to each of the knowledge management processes. The results showed a good model fit for all the knowledge managerial processes. Then the data were explored, analyzed and compared with the current status of KM practices with respect to their sizes. It is found that size has a profound impact on the extent of adoption of KM practices.